Identité professionnelle des formateurs d’enseignants de Lycée Professionnel en IUFM : enjeux et dilemmes à l’heure des réformes - Thérèse Perez-Roux (Recherches en Éducation)
The article focuses on the professional identity of vocational school teacher trainers, as new training courses given by universities and leading to a Master’s Degree are about to start. Two qualitative surveys were conducted in 2007 and 2009 among teacher trainers within the same IUFM. The results obtained in 2007 give an insight into the way those professionals defined their missions, sharing some common ground with other teacher trainers, but also claiming specificity. The 2009 survey reveals an evolution. The reorganizing of teacher training which is about to take place generates uncertainties about the future. The study shows that teacher trainers feel worried about their integration and legitimacy. It stresses the necessity of redefining professional activity. At the heart of teacher trainers’ preoccupations lies recognition. What they say reveals the place they have had so far in our institution. This place, which will have to be re-negotiated in the near future, generates a whole range of attitudes within the group which has been surveyed.